2014
DOI: 10.1111/rec.12147
|View full text |Cite
|
Sign up to set email alerts
|

Nesting Habitat Creation Enhances Recruitment in a Predator‐Free Environment: Malaclemys Nesting at the Paul S. Sarbanes Ecosystem Restoration Project

Abstract: Aquatic turtles worldwide are plagued with habitat loss due to development and shoreline alteration that destroys the terrestrial–aquatic linkage which they must cross to reproduce successfully. Furthermore, nesting habitat loss can concentrate nesting, increasing nest predator efficiency. We describe how the Paul S. Sarbanes Ecosystem Restoration Project at Poplar Island created nesting habitat for Malaclemys terrapin (Diamondback Terrapin), and document nesting success in response to construction progress an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…Dam construction harms turtle populations by disrupting gene flow, through habitat deterioration (especially of nesting sites) and by interrupting migratory routes [51,52]. Channelization of rivers and shoreline hardening may eliminate nesting and basking areas and alter the hydrodynamic processes that maintain critical nesting habitat [53]. At least 48% of the global river volume has been altered by flow regulation or fragmentation by impoundment structures [54].…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Dam construction harms turtle populations by disrupting gene flow, through habitat deterioration (especially of nesting sites) and by interrupting migratory routes [51,52]. Channelization of rivers and shoreline hardening may eliminate nesting and basking areas and alter the hydrodynamic processes that maintain critical nesting habitat [53]. At least 48% of the global river volume has been altered by flow regulation or fragmentation by impoundment structures [54].…”
Section: Reviewmentioning
confidence: 99%
“…It may also compromise their population genetics if some nest areas are better protected than others [103], although the longevity and high fecundity of many species may offset genetic issues [195]. Head-starting has been credited with increasing recruitment for populations of some species (e.g., Kemp's Ridley, Lepidochelys kempi [196]; Diamondback Terrapins [53]), but follow-up studies are needed. The long-term success of head-starting has not been widely evaluated quantitatively; deterministic and stochastic modeling suggest it will not save declining populations (e.g., [197]; [6] for marine turtles; [48,67,198] for freshwater turtles).…”
Section: The Pet Trade and Captive Breeding For Conservationmentioning
confidence: 99%
“…Feinberg and Burke (2003) recorded highest depredated terrapin nest densities on man-made trails. Roosenburg et al (2014) demonstrated that terrapins will sometimes use artificially produced habitats for nesting with some success. The nesting activity associated with the Goffinsville and Holly Point boat ramps would not be possible without the construction associated with the ramps.…”
Section: Discussionmentioning
confidence: 99%
“…Barriers such as roads and bulkheading can also lead terrapins to nest in marginal habitats (Roosenburg ) such as backyards and driveways. Such displacement is of particular concern as human development increases because it may lead to lower nest success (Roosenburg , Roosenburg et al ) and population declines.…”
Section: Discussionmentioning
confidence: 99%
“…The creation of artificial nesting habitats could also be used to offset the creation of barriers to natural nesting areas (Baldwin et al ). For example, Roosenburg et al () describe the restoration of an offshore island within the Chesapeake Bay, Maryland that has created productive nesting habitats for terrapins away from the complex threats present around mainland nesting sites. Knowing that terrapins will use artificial nesting habitats, we recommend their development in Barnegat Bay from washed dredge soils (Wnek et al ).…”
Section: Management Implicationsmentioning
confidence: 99%